The Miraculous Nature of the Qur'an in Contemporary Scientific Proof from the Perspective of Islamic Communication - Pratiwi, Sry Hayani; Bakar, Achmad Abu; Galib M, Muhammad (State Islamic Institute of Bone, Indonesia, 2024)
The Qur’an has become a fascinating subject of research for scientists and scholars, both in the Islamic world and beyond. In this study, we explore the miraculous nature of the Qur’an that remains relevant in contemporary scientific contexts through a literature review method..The miraculous nature of the Qur’an can be defined as an extraordinary phenomenon that confirms the prophethood of a prophet. This includes verses that describe the creation of the universe and mankind, such as those found in Surah Al-Anbiya’ (21:30), Surah Yunus (10:5), Surah Ar-Rad (13:2), Surah Al-A’raf (7:54), Surah Al-Hajj (22:65), Surah Az-Zumar (39:6), and Surah Al-Mu’minun (23:12-14).Many scholars are drawn to the scientific interpretation of the Qur’an, considering it relevant to the modern era. The Qur’an is regarded as Allah’s revelation that provides guidance for humanity, with its scientific content seen as a divine gift. This highlights the importance of Islamic communication theory in understanding and appreciating the wisdom of the Qur’an and supporting the truth of Islamic teachings.Thus, the Qur’an not only strengthens faith but also provides a solid scientific foundation, reflecting its miraculous relevance and significance in the context of modern scientific evidence.